Novel probiotics from kefir drinks - Tan, Yoke Hun (Nanyang Technological University, 2020)
Kefir is a type of fermented milk and water beverage where the fermentation process is done due to the activities of bacteria and yeast in the kefir grains. In many studies, it has been found that many of the bacteria found in the kefir grains are potential probiotics which could be used in future healthcare industry as potential health supplements. This project is focused on screening novel isolates from kefir grains for the potential probiotic properties. Within the 236 strains isolated during a previous FYP project, we first narrowed down the initial screening to 40 strains which consists of 36 different species as well as 3 controls. In the initial stage, antimicrobial screening against commonly found pathogens was done using these 36 species to identify which strains exhibits antimicrobial behaviours. Next, these strains also undergo a cholesterol assimilation assay as well as hydrolysis of bile salt hydrolase assay to identify if these isolates display probiotic behaviours. Finally, the isolates that showed positive results are then tested for their ability to survive in a simulated environment of the human digestive system.